DETERMINATION OF THE ORIENTATION OF THE ACCRETION COLUMNS IN MAGNETIC CATACLYSMIC VARIABLES - Andronov, I. L (Одеські астрономічні публікації, 2017)
Methods for the determination of the orientation of accretion columns in magnetic cataclysmic variables based on the observations of the circular and linear polarization, X-Ray flux and profiles of emission lines are discussed. The non-uniformity of the density distribution through cross-section of the accretion columns leads to significant changes in the resulting spectra in two polarizational modes as compared with the ’homogeneous plasma slab’ model. Simplified expressions for the circular polarization provides an additional relation between the inclination i and the magnetic latitude b. Similar relations ma e established from the X-Ray and spectral observations. However, by interchanging the values of i and b, one will obtain the same phase relationship. The only direct method obtain the true values for i and b is based on polarization position angle changes. Real columns are non-stationary and not axisymmetric, which significantly affect observe characteristics. Observations of polars show long-term orientation changes of the accretion column with respect to the binary system. However, observations to date do not allow one to distinguish between the ’swinging’ and ’idling’ dipole models.